2013
DOI: 10.1094/pdis-08-12-0788-re
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crop Rotations and Tillage on Pratylenchus spp. in the Semiarid Pacific Northwest United States

Abstract: Smiley, R. W., Machado, S., Gourlie, J. A., Pritchett, L. C, Yan, G. R, and Jacobsen, E. E. 2013. Effects of crop rotations and tillage on Pratylenchus spp. in the semiarid Pacific Northwest United States. Plant Dis. 97:537-546.There is interest in converting rainfed cropping systems in the Pacific Northwest from a 2-year rotation of winter wheat and cultivated fallow to direct-seed (no-till) systems that include chemical fallow, spring cereals, and food legume and brassica crops. Little information is availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…in rangeland. Where nematode densities have become elevated in expiring conservation programs, it is suggested that poor or nonhost crop species such as barley, safflower, flax, brown mustard, or selected cultivars of pea or chickpea (30,37) be planted as a transition crop before planting the first crop of wheat. It is also likely that occurrences of specific weeds at any time in the cropping system can elevate densities of Pratylenchus spp.…”
Section: Discussionmentioning
confidence: 99%
“…in rangeland. Where nematode densities have become elevated in expiring conservation programs, it is suggested that poor or nonhost crop species such as barley, safflower, flax, brown mustard, or selected cultivars of pea or chickpea (30,37) be planted as a transition crop before planting the first crop of wheat. It is also likely that occurrences of specific weeds at any time in the cropping system can elevate densities of Pratylenchus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Barley (Hordeum vulgare L.) cultivars are generally more resistant than commercial wheat cultivars (34)(35)(36)(37). While wheat is by far the dominant economically viable rainfed crop in the lowprecipitation zone of the PNW (32), field studies with potential rotation crops have provided insights of root-lesion nematode dynamics in dryland cropping systems (41). For instance, Pratylenchus spp.…”
mentioning
confidence: 99%
“…For instance, Pratylenchus spp. densities were typically suppressed when barley was produced, as compared to canola (Brassica campestris L. and B. napus L.) or wheat (40,41,46). In low-precipitation regions, growers often report higher wheat yields when wheat follows barley compared to wheat planted after wheat, canola, or chickpea (Cicer arietinum L.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pythium diseases caused by multiple species are particularly prevalent in direct-seed systems when seed is planted into cool, wet soil (10,15,22,36,57). Root-lesion nematode {Pratylenchus neglectus and P. thornei) densities are strongly influenced by the frequency at which hosts are produced in the cropping system and are more prevalent in cultivated than in direct-seed systems and following wheat compared with barley (53,54). tritici) occurs regularly and is most prevalent in annual crops and in direct-seed systems (12,14,29,36,38,50).…”
mentioning
confidence: 99%